PENGEMBANGAN MEDIA ANIMASI BERBASIS CANVA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS VI SDN 166321 TEBING TINGGI - Sitepu, Zulhijjah Febriyani; Masta Marselina Sembiring; Halimatussakdiah; Edizal Hatmi; Dody Feliks Pandimun Ambarita; Dila Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to produce valid, practical, and effective Canva-based animation video learning media in Indonesian language subjects on compound sentences in class VI SDN 166321 Tebing Tinggi. This research is Research and Development using a 4D development model consisting of define, design, development, and disseminate. The subjects of this study were 22 class VI students of SDN 166321 Tebing Tinggi. The data analysis technique in this study was qualitative data obtained from interviews, responses, and suggestions from material validators, media, and education practitioners, while quantitative data was obtained from questionnaires given to material experts, media experts, and education practitioners. The results of the study showed that the assessment of validity by material experts obtained a score of 46 (90%) with the criteria of